2023
DOI: 10.7717/peerj.15019
|View full text |Cite
|
Sign up to set email alerts
|

Roles of cuproptosis-related gene DLAT in various cancers: a bioinformatic analysis and preliminary verification on pro-survival autophagy

Abstract: Background Studies have shown that the expressions and working mechanisms of Dihydrolipoamide S-acetyltransferase (DLAT) in different cancers vary. It is necessary to analyze the expressions and regulatory roles of DLAT in tumors systematically. Methods Online public-platform literature on the relationships between DLAT expression levels and tumor prognosis, methylation status, genetic alteration, drug sensitivity, and immune infiltration h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Through our analysis of TCGA ESCA and GSE63941 data sets, we found a correlation only between expression levels of DLAT and METTL3. Furthermore, we observed that DLAT expression was significantly higher in tumour samples compared to normal samples, consistent with previous reports indicating DLAT upregulation in various types of cancer such as LIHC, LUAD, LUSC, PAAD and STAD [72][73][74][75]. Additionally, we found that DLAT expression was significantly higher in the high METTL3 expression group than in the low expression group, highlighting the potential association between these two genes in cuproptosis-related tumour development.…”
supporting
confidence: 91%
“…Through our analysis of TCGA ESCA and GSE63941 data sets, we found a correlation only between expression levels of DLAT and METTL3. Furthermore, we observed that DLAT expression was significantly higher in tumour samples compared to normal samples, consistent with previous reports indicating DLAT upregulation in various types of cancer such as LIHC, LUAD, LUSC, PAAD and STAD [72][73][74][75]. Additionally, we found that DLAT expression was significantly higher in the high METTL3 expression group than in the low expression group, highlighting the potential association between these two genes in cuproptosis-related tumour development.…”
supporting
confidence: 91%
“…The relationships between DLAT and various types of tumors have been extensively studied. It has been found that mRNA levels of DLAT are significantly higher in tumor tissues of liver hepatocellular carcinoma and stomach adenocarcinoma compared to normal tissues, whereas they are lower in head and neck squamous cell carcinoma and kidney renal clear cell carcinoma (Yang et al 2023). DLAT expression has also been identified as a prognostic factor in several cancers, where higher levels are associated with poorer survival outcomes (Xu et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a study has shown a correlation between cuproptosis-related dihydrolipoamide S-acetyltransferase (DLAT) and CD49d, which is one of the typical phenotype markers of Tregs. The high expression of DLAT may increase the immune infiltration of Tregs; thus, tumorigenesis and tumor invasion are ultimately promoted [ 62 ]. In sum, both cuproptosis and ferroptosis are involved in the regulation of TME in liver cancer; but for now, few currently verify the effect of cuproptosis federation with ferroptosis on TME in liver cancer.…”
Section: Immunomodulation Of Cuproptosis and Ferroptosis In Liver Cancermentioning
confidence: 99%